International classification of diseases : manual of the international statistical classification of diseases, injuries, and causes of death. - World Health Organization (Geneva : World Health Organization, 1977)
Naslagwerk van de WereldGezondheidsOrganisatie als hulp bij het benoemen van ziekten.
2. Alphabetical index